Traditional Game of Ular Naga for Early Childhood Development from Teacher’s Perspective - Pramudyani, Avanti Vera Risti (Perkumpulan Pengelola Jurnal PAUD Indonesia, 2020)
The traditional game Ular Naga is one of the traditional games from the Yogyakarta region, these games can be a method to create joyful learning and can develop many aspects of early childhood. This study aims to know the benefit of traditional games of Ular Naga for early childhood teacher perspective in early childhood education. This research is qualitative research with early childhood teacher as the subject and to collecting the data with the interview, observation, and documentation. Validation data used triangulation technique. Analysis of data such as collected data, reduction data, display data and make a conclusion. The result shows that the majority of the teacher's perspective has the same argument that Ular Naga has the benefit of developing an aspect of the children such as gross motor skills with activities walking, running, catching, make a train, and make a line and social-emotional aspects with activities build cooperative within friends in the group. However the teacher not yet explanation holistically all the aspect that should be can develop from Ular Naga.